PUBLIC OPINION AND DELIBERATIVE DEMOCRACY - Cristina, Llano Hermida (Anales Universitatis Apulensis Series Jurisprudentia; No 16 (2013): ANNALES UNIVERSITATIS APULENSIS - SERIES JURIPRDENTIA, 2013)
I analyze the prerequisites for the existence of public opinion in society, reflecting on whether the absence of prejudices should be one of these. At the same time, I delve, among other questions, into the process of forming public opinion, to what degree public opinion acts as a control or brake on political power, and on the role of intellectuals in the context of a deliberative democracy. KEYWORDS: public opinion – democracy – deliberation – freedom of expression – equality – political pluralism – power – control - social change – prejudices – education – comunication media – intellectuals